THE EFFECT OF PHSYCO EDUCATION ON POST PARTUM DEPRESSION: LITERATURE REVIEW - Erien Luthfia; Hadi Kusuma Atmaja (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2020)
Background: The responsibility that is carried out as a mother after giving birth to a baby becomes a conflict within women. Some mothers fail to adapt to these changes and experience psychological problems. The existence of various potential stresses in pregnancy and childbirth may be the cause. This condition is known as postpartum depression. Early detection and good early treatment is needed to prevent more severe depression. This study aims to determine the effect of phsyco on the incidence of post partum depression.Methods: This study used a literature review design by collecting data from a computerized database search study (PubMed, BMC, Cochrain, Google Scholar) in the form of research journals and review articles in the last ten years.Results: Based on the various literature reviews that have been presented, there is an effect that offers Phsyco Education on post partum depression.Conclusions: there is an effect of educational interventions on the incidence of post partum depression. It is hoped that the next researchers will use the basic data of this literature review as a reference frame for further research and provide initial information for the development of similar research.